Selected aspects of PPP: Experience of Poland and Kazakhstan - Bednyakova, Olga (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The PPP is a complex phenomenon which embraces social, economic, politic, legal and other spheres. It is necessary for PPP centers to emerge as they facilitate the understanding of the PPP role in the economic development and promoting growth. The statuses of these centers vary and depend on the whole PPP policy of a given country. The comparison of the basic law concerning PPP centers in Poland and Kazakhstan reveals the diverse approaches to it in these two countries.
Keywords: public-private partnership; government role; economic development; PPP in Poland and Kazakhstan